COVID-19: Recent advances in epidemiology, virology, etiopathogenesis, clinical trials and vaccine development - Banerjee, Indrajit; Mohabeer, Poormasha; Shukla, Ananya; Kashyap, Abhishek; Robinson, Jared (Journal of Biomedical Sciences, 2020)
Background:The causative virus of COVID-19 has been named SARS-CoV-2. It is the seventh coronavirus that is pathogenic to humans and the third in the series of human pathogenic beta coronaviruses. Patient zero was identified to have contracted the virus in Wuhan, China. Shortly after the initial identification of the virus and its symptoms, multiple studies concluded that the virus originated from the “Wuhan seafood market”, a notorious market place for illegal wildlife trade based in Wuhan, a city in the Hubei region of the People’s Republic of China. Globally, as of 7:02 pm CEST, 29 May 2020, there have been 5704736 confirmed cases of COVID-19, including 357736 deaths, reported to the WHO. The transmission of COVID-19 is primarily by way of respiratory droplets, which can be developed via means of coughing or sneezing, hence spreading the disease from one person to another person. The research proposed indicates the possibility of bats as being the natural cistern of SARS-CoV-2, hence making COVID-19 a zoonotic disease. The most suspected intermediate host is the Malayan pangolin. SARS-CoV-2 is a single-stranded RNA virus that has an affinity for ACE2 receptors in humans, causing severe pathological symptoms. Symptoms like anorexia, dyspnea, fatigue, pyrexia, cough, headache, dizziness, nausea, productive sputum, abdominal pain, myalgia, sore throat, diarrhea, and vomiting. Vaccines that are currently in the clinical evaluation are the Adenovirus type 5 vector, mRNA-1273, Inactivated alum, ChAdOx, LNP-mRNA, DNA plasmid vaccine with electroporation and Inactivated vaccines. A Phase III randomized multicountry clinical trial comprising of 100 countries known as “Solidarity” (ISRCTN83971151) has been initiated by the WHO to achieve the unified goal of producing an adequate treatment for COVID-19. The present Solidarity trial focuses on the following drugs: Remdesivir, Lopinavir/Ritonavir with or without interferon beta-1a, Chloroquine, or hydroxychloroquine. Conclusion: It is invariably essential to promote research in this field of study and find an appropriate solution to the virus to allow individuals worldwide to lead a secure and healthy life.